Public Health Significance of Rotavirus Gastroenteritis - Osazee Ekundayo Izevbuwa (Jinnah University for Women, 2021)
Background: Rotavirus is a type of virus that lacks the membranous layer (envelope); belonging to the family Reoviridae. Rotavirus derived its name from its characteristic appearance of a wheel like structure, as revealed by electron microscopy. This virus has been known for many years as the causative agent of inflamed stomach and intestines among children, which can spread by fecal-oral transmission and clearly exhibit itself with abdominal pains, increased urge to vomit, headache, feeling of discomfort, fever  and severe diarrhea. Therefore, treatment of the infection is primarily targeted. There are two vaccines; Rotarix and RotaTeq, have been developed to stop the viral infection. The administration of Lactobacillus spp. is an additional treatment regime, to reduce the time of the severe stooling.